Spectrophotometric Determination of Thymol in Pharmaceutical Preparations Via Oxidative Coupling Reaction with 2,4- dinitrophenylhydrazine in the Presence of Potassium Periodate - Fadhil, Ghadah (Iraqi Journal of Science, 2023)
A new, simple and sensitive spectrophotometric method for the determination of Thymol in pure and mouth wash preparations has been proposed in this study. The method was based on oxidation of 2,4-dinitrophenylhydrazine with potassium periodate and coupling with Thymol in alkaline medium to form an intense violet water-soluble dye that is stable and has a maximum absorption at 570 nm. A graph of absorbance versus concentration shows that Beer’s law was obeyed over the concentration range of 0.25-10 μg.mL-1 of Thymol, with detection limits of 0.063 μg.mL-1. All experimental parameters that affect the development and stability of the colored product were carefully studied and the proposed method was successfully applied to the determination of Thymol in mouth wash preparations.